Microbiological quality of surimi-based imitation crab - SOULTOS (Ν. ΣΟΥΛΤΟΣ) N.; ABRAHIM (Α. ΑΜΠΡΑΧΙΜ) A.; THEOLOGIDOU (Ε. ΘΕΟΛΟΓΙΔΟΥ) E.; KARAIOANNOGLOU (ΠΡ. ΚΑΡΑΪΩΑΝΝΟΓΛΟΥ) Pr.; KANSOUZIDOU (Α. ΚΑΝΣΟΥΖΙΔΟΥ) A. (Journal of the Hellenic Veterinary Medical Society, 2018)
A survey was conducted to evaluate the microbiological quality of sliced, vacuumpacked, surimi-based imitation crab at the retail level, during a 3-month storage period. The roll shaped product imported from France, was sliced and packed in a fishery processing plant in the region of Thessaloniki. Twenty five samples were examined each month, and a total of 75 samples were examined during the three month storage period of the product. Psychrotropic, lactic acid and coliform bacteria, Escherichia coli I, yeasts, Staphylococcus aureus, Salmonella spp., Listeria spp. and Escherichia coli Θ157:Η7, were used as microbial indices, to evaluate the microbiological quality of the product. The following conclusions were derived from the evaluation of the results of the microbiological examinations. 1) The microbiological condition of the crab meat analogs examined on the 15th day of storage, was found satisfactory, since microbial populations were very low, while pathogenic bacteria were not detected in any of the examined samples. 2) The overall microbiological quality of the samples examined at the end of the second month of storage, was also good, since psychrotrophic and lactic acid bacteria exceeded 1Θ7 log cfu/g only in one sample), while coliform bacteria were not detected in 60% of the samples and Escherichia coli I was detected only in one sample. The mean value of the yeasts was 2.84 log cfu/g, while molds were not detected in any of samples examined. 3) The microbiological quality of the samples examined at the end of the three months storage period was not satisfactory, since the microbial indices in the majority of the samples (80%), were rather high. S. aureus, Salmonella spp, Listeria s pp. and E. coli 0157:H7 were not detected in any sample, during the three month storage period.